Negotiating sexuality in Grahamstown East: young black women's experiences of relationships in the context of HIV risk,Negotiating sexuality in Grahamstown East: black women's experiences of relationships in the context of HIV risks - Clüver, Frances Rose Mannix (Rhodes University, Faculty of Humanities, Department of Psychology, 2010)
Adolescent sexual health has been identified as a significant health and development problem facing South Africa. Limited amounts of research on sexual interactions have been undertaken, with information on adolescents' romantic relationships being particularly scarce. Qualitative research needs to foster an understanding of the dynamics of sexual interactions in specific settings, and with emphasis in the past on cognitive health psychology models, very little is thus known about how adolescents negotiate and make sense of their sexual experiences. This highlights the need to investigate the complexities of human sexuality in a contextual manner. In response, this study explores the lived experiences of four young black women as they negotiate their agency and sexuality in a local context. By way of in-depth qualitative interviews, which were analysed for recurrent themes using interpretative phenomenological analysis, this project examines the participants' experiences regarding sex, relationships, communication, sexual health care, as well as HIV and pregnancy prevention. The results reveal that communication about sexuality in the participants' homes was limited if not absent altogether. When seeking sexual health care, they found clinic nurses to be judgemental and rude. Regarding sexuality and HIV education, the participants stressed the need for outside educators to teach in more practical ways to increase efficacy. In their dating relationships, most participants revealed their boyfriends had a great deal of influence over their sexual initiation. Unwanted pregnancy surfaced as a greater fear than HIV in their accounts due to pressure to finish their education and attain well-paying jobs in the future. The participants felt unable to stop their boyfriends' infidelity and had limited agency when facing sexual demands. Their accounts revealed that they negotiate their agency in an atmosphere of coercion and the threat of rape. However, areas of agency included their consistent condom use even when facing pressure to have unprotected sex, and their active accessing of sexual health services for hormonal contraception. These insights serve to better inform sexual and reproductive health education and intervention programmes for young women. Moreover, educators, researchers and programme developers alike may gain useful insights from the personalised accounts derived from this study.
Keywords: HIV infections -- South Africa -- Grahamstown; Man-woman relationships -- South Africa -- Grahamstown; Intimacy -- South Africa -- Grahamstown; Sex -- South Africa -- Grahamstown; Youth, Black -- South Africa -- Grahamstown -- Sexual behavior; HIV infections -- Social aspects -- South Africa -- Grahamstown; Youth, Black -- South Africa -- Grahamstown -- Attitudes; Reproductive health -- South Africa -- Grahamstown; Health education -- South Africa -- Grahamstown; Youth, Black -- South Africa -- Grahamstown -- Health and hygiene; Phenomenological psychology